Vertical air profiling in False Bay - Maritz, Benita (Department of Oceanography, 2020)
Marine surface layer micrometeorology mainly constitutes vertical turbulent fluxes of parameters such as momentum, heat, water vapour and aerosols. These turbulent fluxes have been tested in the laboratory and can be applied to the atmospheric changes over the ocean, where wind speed, the air-sea temperature difference (ASTD) and humidity play a major role. Due to the difficulty of actually measuring these changes directly, equations were derived that describe the micrometeorology in terms of actual meteorological observations. The theory of micrometeorology in turn provided the accepted calculations to predict vertical profiles for wind speed, air temperature and humidity. Nevertheless, using micrometeorology theory to predict atmospheric conditions over the ocean proves to be more difficult than over land. This is mainly due to the complex nature of the oceanic environment and its interaction with the atmosphere directly above it. The primary objective of this work was therefore to investigate the potential of deploying a Helikite in order to characterise the lower atmosphere in False Bay. Focus was placed on the methods to correctly measure air profiles over the ocean up to a maximum height of 200 m. A description of the system set-up, data acquisition, deployment parameters and data analysis are discussed. The second objective was to evaluate the micrometeorology theory used in a micrometeorological model for the marine surface layer with False Bay data. This was achieved by using experimental data to run the model. The model output was then compared to the experimental profile measured as part of objective one. The micrometeorological model it aimed to assess is based on the standard bulk meteorological observations of wind speed, temperature, humidity and the turbulent fluxes of momentum, heat and water vapour. Analysis of the various environmental parameters showed a complex oceanographic and atmospheric system. The air profiles recorded for this study were recorded in an area where smaller scale local effects were dominant, which could explain some of the discrepancies encountered when attempting to reproduce the measured profiles using micrometeorology bulk parameterisations. The four profiles described in this thesis were grouped with two profile days showing a good comparison between the predicted and measured profiles. Results also indicated that micrometeorology theory perform better when using the ‘bucket’ Sea Surface Temperature (SST) at 0.5 m below the surface.